Polgárok egy sváb faluban. A két világháború közötti Németbóly társadalmának alapvonásai - Kovács, Katalin (Tér és Társadalom, 1990)
The present paper describes the most important characteristic features of local society in a (local) central village in Baranya county between the two World Wars. That time the village was called Németbóly, and it is Bóly today. The two, probably interconnected, most important features of íts local society to be mentioned: the exceptionally high level of bourgeois development and social organization. The latter took form mostly in organizations initiated from the „top" and the control of associations also remained in the hands of the local élite (priests, teachers, „the elderly" or „the authorities"), nevertheless they still had a fundamental role in consciousness- formation. The associations of both peasant and artisan youth were characterized by „upward levelling", at least as far as the appearance, clothing and behaviour were concerned, and thereby they indeed did play the role of „social group formation": the rules were obligatory for everyone, the officials were elected by secret vote, clothing standards facilitated to hide financial differentials, and all this raised the self-esteem of the members of associations. Organizations operated by and for men reflected an almost balanced and symmetric structure along three axes: profession, age and authority. Thus e.g. the youth associations of artisan and peasant bourgeois, who represented roughly similar proportions in the community, operated so that they were linked to the organizations of adults via their supporting members and the leaders elected from among them. Peasants and artisans could delegate the same number of members to the communal corporation. There has been also an informal form of social meetings, which is still lively nowadays, the „wine-cellar club". 6-8 men, usually of the same age, formed these clubs, who spent an evening a week together talking, singing, playing cards, and of course, drinking wine, in one of the wine-cellars in the outskirts of the village. Girls from age 6 to 18 were supervised by the Sisters of Mercy who organized their spending the leisure time as it was thought to be the most proper, most useful and most beautiful, grouping them into six „societies" by age. Taking into account the symmetric arrangement of various informal groups, associations and clubs–organized from the top or self-organized–by their members’ sex, we can fend a major asymmetry to the men’s benefit, since married women had no organized social life at all. Members to associations were accepted regardless of their wealth differentials, on the basis of their status defined by occupation alone. This stood for the richest artisan and peasant bourgeois, too, who could also be members of the casino, which "consecrated" the order of the rich, íf this was in line with, or even desireable for, the individual taste and family aspirations for the future. The „order of the rich" also included wealthy artisan bourgeois of Németbóly who claimed the title of „gentleman" besides their status in economic lífe acquired on the market, or in a wider sense: who claimed a social prestige being in harmony with their fortune. The „order of the rich" was therefore a relatively open formation based on lifestyle and prestige, it was organized besides class status, while the other, the peasantry, which preserved feudal features as reminiscent of the past, formed a closed society, their members being linked together much more by an admitted lifestyle than a desired one. This lifestyle places work and austerity in its focus, which could only be accepted with a peasant sense of vocation, but its fruits were incontestable: the widest stratum of peasant society in Németbóly was made of well-to-do farmers having 30-70 acres of land. The bourgeois values of hard-work and austerity were the ordering values of not only the peasants’ but also the artisan bourgeois’ lifestyle, and it was thanks to the overall prevalence of these values that the level of bourgeois development in Németbóly was relatively high when compared to its usual level in Hungarian villages between the two World Wars. All this is obviously not independent of the fact that it is about a settled German Catholic community in which the „settlers’ ethos", having the above values in its very centre, was a long affecting factor. The relatively balanced division of labour between men and women also characterizing other German settlers’ communities much more than any other ethnic groups, and the production structure going beyond the limited local market, fitting in directly a wider circulation system, also contributed to the formation and christallization of a bourgeois-type structure of production and consumption. The dominance of autonomous households and firms, the wide spectrum of self-reliant organizations and social groupings were the attractive features of the local society in Németbóly between the two World Wars because they represented sings of an advanced stage of bourgeois development. At the same time, eternal loyality to superiors, anti-liberalism, an overall prevalence of the principle of authority and paternalism saturating all contacts and relationships, as well as the related relative scarcity of autonomous personalities, were undoubtedly also present in the local society of Németbóly of the time. And since the war and then fourty years intervened, one cannot teli what would have happened if... , one can only hope that the previous features have become more marked while the latters have reduced in number.